HLA desensitization based on results of the luminex technique in kidney transplant – A single-center experience - S B Bansal (Wolters Kluwer Medknow Publications, 2021)
Background: There is little experience of human leucocyte antigen (HLA) desensitization in India based on the Luminex single-antigen bead (SAB) testing. We retrospectively analyzed our patients, who underwent HLA desensitization based on Luminex SAB results. Method: Between 2014 and 2018, patients with complement-dependent cytotoxicity cross-match (CDC-XM) negativity but flow cytometry crossmatch (FC-XM) positivity were further analyzed with Luminex SAB for donor-specific antibodies (DSAs). A total of 12 patients who had DSA mean fluorescent intensity (MFI) of >1000 and <10,000 were included in the study. Our protocol for desensitization consisted of plasmapheresis (PP) followed by low dose intravenous immunoglobulin (IV IG) 100 mg/kg and induction with antithymocyte globulin (ATG). Patients were taken for transplant when either MFI was <1000 and/or FC-XM was negative. Results: All 12 patients were first transplant and 10 had a history of some sensitizing event; pregnancy in 4, blood transfusions in 4, and both in 2 patients. FC-XM was positive for T-cell in 4, B-cell in 6, and both in 2 patients. On evaluation by Luminex SAB, 6 patients had MFI from 1000 to 2000, and 6 had MFI of >2000. All underwent desensitization successfully. Two patients had an increase in posttransplant DSA titers requiring posttransplant PP. The mean follow-up was 26.6 ± 13.9 months. On follow-up, only one patient developed acute T cell-mediated rejection 1 year after transplant, which responded to pulse steroids. There was no graft or patient loss until the last follow-up. Conclusion: This study shows that HLA desensitization is feasible and successful in the Indian setting if patients are properly selected.